ALTERNATIVE BUSINESS INCOME CONTRIBUTION IN SUPPORTING HOUSE HOLD INCOM KELURAHAN PURNAMA SUBDISTRICT DISTRICT DUMAI CITY WEST RIAU PROVINCE - Tria Nurmala Sari; Lamun Bathara; Darwis Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in April 2017 on the Kelurahan Purnam of Dumai Barat subdistrict Dumai City in Riau Province. Its was aimed to identify the types of work done by fishermen households in Kelurahan Purnama, to determine the income of fishermen households obtained from fishing and alternative business in supporting the household income of fishermen, To know the contribution of alternative business to household income of fishermen, To analyze the influence of socio-economic characteristics of fishermen in Kelurahan Purnama to alternative income household fishermen. The method used by survey methods, of direct observation of the object in the field and data collection through interviews with fishermen.Based on the research results can be found that alternative of fisherman households in Kelurahan Purnama consists of non-fish traders to open daily stalls), become harbor laborers and plantation workers, gardeners, traveling traders, mobile phone keepers, buildings, and honorariums, from the result of fishing effort that is 1,570,000 - Rp 2,460,000 / month and the income of alternative business is Rp 775.000 - Rp 2.175.000 / month, the characteristic that influence fishermen economic condition on alternative business that is age, education, work experience, the number of dependents, and the bulk of working hours, while the contribution of income received from fishing business is 58.05%, while the contribution of income from alternative business is 41.88%. Keywords: Contribution, Alternative Business, Household Income, Kelurahan Purnama